Low‐dose fixed‐target serial synchrotron crystallography. Issue 4 (1st April 2017) - Owen, Robin L.; Axford, Danny; Sherrell, Darren A.; Kuo, Anling; Ernst, Oliver P.; Schulz, Eike C.; Miller, R. J. Dwayne; Mueller-Werkmeister, Henrike M.
Abstract : A time‐ and sample‐efficient approach for the serial collection of room‐temperature diffraction data using a fixed target at a synchrotron is demonstrated. Abstract : The development of serial crystallography has been driven by the sample requirements imposed by X‐ray free‐electron lasers. Serial techniques are now being exploited at synchrotrons. Using a fixed‐target approach to high‐throughput serial sampling, it is demonstrated that high‐quality data can be collected from myoglobin crystals, allowing room‐temperature, low‐dose structure determination. The combination of fixed‐target arrays and a fast, accurate translation system allows high‐throughput serial data collection at high hit rates and with low sample consumption.